Research on multiscale simulation-guided development of physical adsorption in environmental engineering - Zhang Yongqi; Zhang Jin; Tao Siyue (EPJ Web of Conferences)
Physical adsorption technology has regarded as an efficient, simple and cost-effective approach in the field in environment. In this research, the mechanisms, application theory and development of physical adsorption technology in the environment was systematically analysed by taking fluorine pollution as an example. Among the adsorption materials, the metallic materials have extremely high application advantages. With the development of adsorption technology, the surface and structure modification of adsorption materials and the enhancement of the synergy of different effects to improve adsorption performance are the keys to the physical adsorption technology. For further research, it is proposed that prioritize atomic-level active site design, develop adsorption-catalysis synthetic systems, low-carbon regeneration technology, and high efficiency and intelligence technologies should be think as the main development toward the physical adsorption in environment.